Being a Woman in the American Slavery System: A Study of The slave Woman’s Ordeal in America, from 1776 to 1865 - AGUESSY, ANNE NATHALIE JOUVENCIA AGOSSI; KOMBIENI, Didier; Assongba, Belmonde (My University, 2020)
Women have long been negatively stereotyped in every society, usually portrayed as submissive and passive. In the case of the black women in the slavery context, the conception of them by their male compatriots as well as the white master is dual: a working animal to do every chore in the household in the one hand, and an object for the master’s sexual appetite in the other hand. Scholars in American slavery have grappled with the question of gender differences among slaves in the Americas in the seventeenth and eighteenth centuries. Whereas some scholars hold that both male and female slaves were assigned different roles, feminist scholars hold that enslaved women labored no less than enslaved men. They observed that unlike white women, female slaves performed the same roles as men slaves. The present research work reveals and analyses the experiences and contributions of slave women in the global American slavery system. As such, the focus is on themes that especially concern female slaves; these include: motherhood, companionship, marriage, work on plantations, and punishment. Central in this study is how those female Blacks experienced slavery in America and how they help build the American economy in that period. Some famous female slave writers such as Harriet Ann Jacobs, Sojourner Truth, and Mary Prince have worked on the issue. Their narratives provide precise information about slaves’ living conditions during slavery, emphasizing on female slave ordeal. It also analyzes the female slave life in the context of their interaction with others and the familial roles they played. It insists on the slave women’s work, their contributions to both male slaves and the masters’ living and social accomplishment. It reveals that when talking about slavery and slave families, authors have put too much emphasis on what men did rather than on what women did and could do. It finds out that the enslaved women made significant contributions to the slave family as well as to the masters’ one, that the slaves’ world was sex-stratified in such a way that the slave women’s world existed independently from the male slave world, and that females rather than males governed slave families. The literary theory applied to the present research is Feminist or Gender Criticism; this is concerned with the ways in which literature (and other cultural productions) reinforce or undermine the economic, political, social, and psychological oppression of women. It is also concerns the role of women in the literary work; the representations of women, the power structures between men and women. On this basis, the assumption is that while “biology determines our sex (male or female), culture determines our gender, masculine or feminine” (Lois Tyson, Critical Theory Today, Pge 53).
Keywords: slavery; female slaves; motherhood; companionship; marriage.